Figurative Repatriation First Nations ‘Artist-Warriors’ Recover, Reclaim, and Return Cultural Property through Self-Definition - Kramer, Jennifer (Journal of Material Culture, 2004)
This article begins with an analysis of the problems of ‘physical repatriation’, as I review the case of the return of a First Nations mask to its community of origin. First Nations struggle to fit their concepts of ownership into western ones, where objects are viewed as alienable. As an alternative, the art of John Powell and Marianne Nicolson depicts a ‘figurative repatriation’ that does not rely on either the courts or museums to recognize legal or moral ownership. I argue that these contemporary artworks are social agents, which bring First Nations cultural objects home by staking out territory within museums. These ‘artist warriors’ forcibly recover (both literally and metaphorically) First Nations objects on display in foreign settings and reinscribe meaning at the level of the personal and the communal. They make objectified assertions of native identity that reclaim the right to self-definition. Moreover, these claims are made all the more powerful through their conscious location within an oppositional discourse framed by the Canadian western art world.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; _Nettoyé

Native Art of the Northwest Coast: A History of Changing Ideas - Townsend-Gault, Charlotte; Kramer, Jennifer (UBC Press, 2013)
This remarkable volume, many years in the making, records and scrutinizes definitions of Northwest Coast Native art and its boundaries. A work of critical historiography, it makes accessible for the first time in one place a broad selection of more than 250 years of writing on Northwest Coast "art." Organized thematically, its excerpted texts are from both published and unpublished sources, some not previously available in English. They cover such complex topics as the clash between oral and written knowledge, transcultural entanglement, the influence of surrealist thinking, and the long history of the deployment of Northwest Coast Native art for nationalist purposes. The selections are preceded by thought-provoking introductions that give historical context to the diverse intellectual traditions that have influenced, stimulated, and opposed each othe
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé